Recombinant L-asparaginase 1 from Saccharomyces cerevisiae: An allosteric enzyme with antineoplastic activity - Costa, Iris Munhoz; Schultz, Leonardo [UNESP]; De Araujo Bianchi Pedra, Beatriz; Leite, Mariana Silva Moreira; Farsky, Sandra H. P.; De Oliveira, Marcos Antonio [UNESP]; Pessoa, Adalberto; Monteiro, Gisele (Springer Nature, 2016)
L-asparaginase (L-ASNase) (EC 3.5.1.1) is an important enzyme for the treatment of acute lymphoblastic leukaemia. Currently, the enzyme is obtained from bacteria, Escherichia coli and Erwinia chrysanthemi. The bacterial enzymes family is subdivided in type I and type II; nevertheless, only type II have been employed in therapeutic proceedings. However, bacterial enzymes are susceptible to induce immune responses, leading to a high incidence of adverse effects compromising the effectiveness of the treatment. Therefore, alternative sources of L-ASNase may be useful to reduce toxicity and enhance efficacy. The yeast Saccharomyces cerevisiae has the ASP1 gene responsible for encoding L-asparaginase 1 (ScASNase1), an enzyme predicted as type II, like bacterial therapeutic isoforms, but it has been poorly studied. Here we characterised ScASNase1 using a recombinant enzyme purified by affinity chromatography. ScASNase1 has specific activity of 196.2 U/mg and allosteric behaviour, like type I enzymes, but with a low K0.5 = 75 μM like therapeutic type II. We showed through site-directed mutagenesis that the T64-Y78-T141-K215 residues are involved in catalysis. Furthermore, ScASNase1 showed cytotoxicity for the MOLT-4 leukemic cell lineage. Our data show that ScASNase1 has characteristics described for the two subfamilies of l-asparaginase, types I and II, and may have promising antineoplastic properties.